2011
DOI: 10.1093/eurjhf/hfq181
|View full text |Cite
|
Sign up to set email alerts
|

Innovative strategy for implementing chronic heart failure guidelines among family physicians in different healthcare settings in Berlin

Abstract: AimsThe aim of this study was to improve drug therapy for chronic heart failure (CHF) patients. Methods and resultsThis prospective interventional pilot study was performed with cross-sectional comparative analysis before and after the intervention. Usual pharmacotherapy was observed for 8 months in two different outpatient healthcare settings in Berlin [11 family physicians from individual GP (IGP) practices and 12 working in a medical care centre (MCC)]. Medical care centres provide a novel structure for out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…A German study from 2011 investigated whether a computer‐based pop‐up reminder system could increase the use of RAS inhibitors, beta‐blockers, and spironolactone in a setting of individual GPs or Medical Care Centres (with GPs and specialists working in the same setting). It was found that beta‐blocker treatment increased significantly by 12.3% to 58.6% and spironolactone by 9.2% to 44.2%.…”
Section: Discussionmentioning
confidence: 99%
“…A German study from 2011 investigated whether a computer‐based pop‐up reminder system could increase the use of RAS inhibitors, beta‐blockers, and spironolactone in a setting of individual GPs or Medical Care Centres (with GPs and specialists working in the same setting). It was found that beta‐blocker treatment increased significantly by 12.3% to 58.6% and spironolactone by 9.2% to 44.2%.…”
Section: Discussionmentioning
confidence: 99%
“…16,[19][20][21] However, patients in these studies could also have been referred for analysis of a heart murmur, or for other cardiac causes of breathlessness.…”
Section: Comparison With Other Literaturementioning
confidence: 99%
“…(continued) applied educational meetings supported by diverse additional methods such as reminders,29,48 networking 33 or distribution55 ; or performed the educational component in the form of an outreach visit, extended by distribution 24 or audit.…”
mentioning
confidence: 99%